Singular perturbation methods applied to a variational problem in greenhouse climate control - van Henten, E.J.; Bontsema, J. (IEEE Conference on Decision and Control, 1992)
The application of singular perturbation methods to a variational problem in greenhouse climate control is demonstrated. An example of economically optimal carbon dioxide control is given. Some preliminary results are shown.< >